STUDI PERBANDINGAN DESAINER INTERIOR DAN DEKORATOR INTERIOR - Dwi Retno Sri Ambarwati (FBS UNY, 2010)
The terms “interior designer” and “interior decorator” are often used interchangeably, as if they were identical professions. Although both may have the ability and talent to create beautiful rooms, the two are not synonymous. Interior decorators are primarily concerned with surface decoration, generally refers to someone who deals with finishes, surfaces, furniture, and wall coverings and no government regulation regarding the work of an interior decorator. On the other hand, an interior designer is one who is trained to create a functional and quality interior environment, qualified through education, experience and examination, so a professional designer can identify and creatively resolve issues and lead to a healthy, safe and comfortable physical environment. Referring to that definition, interior design is the art and science of understanding people’s behavior in order to create functional spaces within the building structures, an in the other hand, an interior decoration is the art of decorating to beautify a space. Although an interior designer can also make aesthetic changes to an interior space, the interior designer is a professional licensed with a licensing authority who coordinates design projects with a holistic approach. This effort includes designing the interior architecture, in addition to beautifying the space. Keywords: interior design, interior decoration, comparative study.